Trading Volume and Belief Revisions That Differ Among Individual Analysts. - Barron, Orie E. (The Accounting Review, 1995)
Examines the empirical association between trading volume and belief revisions that differ among individual analysts. Hypothesis based on relative positions of individual analysts' current and prior forecasts of earnings to measure differential belief revisions.